PENGALAMAN PSIKOLOGIS PASIEN KANKER PAYUDARA DALAM MENJALANI KEMOTERAPI - Fika Aulia; Bardiati Ulfah, Yaolanda Rizqi Agustina, Pratiwi Puji Lestari, Meylinasari (CV. Adiba Aisha Amira, 2024)
The aim of this research is to describe the psychological experience of breast cancer patients undergoing chemotherapy. Researchers want to describe the psychological experience of breast cancer sufferers undergoing chemotherapy so that they can contribute to supporting the healing process of breast cancer sufferers.